Enhanced Acetone Sensing Property of a Sacrificial Template Based on Cubic-Like MOF-5 Doped by Ni Nanoparticles - Ning Zhang; Huijun Li; Zhouqing Xu; Rui Yuan; Yongkun Xu; Yanyu Cui (Nanomaterials, 2020)
Studying an acetone sensor with prominent sensitivity and selectivity is of great significance for the development of portable diabetes monitoring system. In this paper, cubic-like NiO/ZnO composites with different contents of Ni2+ were successfully synthesized by modifying MOF-5 with Ni2+-doped. The structure and morphology of the prepared composites were characterized by XRD, XPS, and SEM. The experimental results show that the NiO/ZnO composite showed an enhanced gas sensing property to acetone compared to pure ZnO, and the composites showed the maximum response value when Ni2+ loading amount was 5 at%. The response value of the 5% NiO/ZnO composite to acetone (500 ppm) at the optimum operating temperature (340 °C) is 7.3 times as that of pure ZnO. At the same time, the 5% NiO/ZnO composite has excellent selectivity and reproducibility for acetone. The gas sensing mechanism of the heterojunction sensor was described.